Letter (copy) : Relief for Spain - Tewson, Vincent
032-0050-001 International HVT/WJB/AC/192 19th May, 1939. Mr. W. Schevenels, International Federation of Trade Unions, 9, avenue d'Orsay, PARIS, VIIe. Dear Comrade Schevenels, RELIEF FOR SPAIN. You know that from time to time you have sent us reports on relief for Spain, in which you listed quantities of various commodities consigned under the auspices of the International Solidarity Fund and outlined the other activities carried on on behalf of the Fund in Spain. The last of these detailed lists was enclosed in your letter of 23rd June, 1938, and you followed this by a survey of the whole work of the Fund in Spain taken up to 1st December, 1938. We are now preparing this section of our Report to Bridlington Congress; you can well imagine the interest of our members in this subject, and our desire to present them the latest information possible. Would it be possible for you to let us have details which brings the latest statement more up to date? I have in mind that you may be preparing a report for the I.F.T.U. Congress, and that such material may be in course of preparation. I may say, of course, that our report will not be issued after your Congress will have met in July next. Yours sincerely, Assistant Secretary. 292/946/32/50